Rozwiąż poniższe równania



Rozwiąż Poniższe Równania class=

Odpowiedź :

Odpowiedź:

[tex]1.[/tex]

[tex]2(m + 5) = 3m[/tex]

[tex]2m + 10 = 3m[/tex]

[tex]10 = m[/tex]

[tex]2.[/tex]

[tex]2(3n - 1) = 5(n - 4)[/tex]

[tex]6n - 2 = 5n - 20[/tex]

[tex]n = - 18[/tex]

[tex]3.[/tex]

[tex]4(4o - 7) = 3(o + 3)[/tex]

[tex]16o - 28 = 3o + 9[/tex]

[tex]13o = 37[/tex]

[tex]o = \frac{37}{13} = 2 \frac{11}{13} [/tex]

Odpowiedź:

Mam nadzieję że dobrze : ]

Zobacz obrazek Hinamimidoricha
Zobacz obrazek Hinamimidoricha